2018
DOI: 10.3390/f9100591
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, Costs, and Selected Environmental Impacts of Remote-Controlled Mini Forestry Crawlers

Abstract: An effective way to reduce off-road traffic in forests is to implement greater distances between skid trails. However, this implies that trees beyond the boom reach of the harvester need to be felled motor manually before being winched to the skid trail, for example using a remote-controlled mini forestry crawler (MFC). They are only a few local studies which have evaluated the performance of such MFCs. The use of MFCs for wood extraction operations in mixed soft- and hardwood stands is presented in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Slope is shown to be a primary factor in productivity because it affects the accessibility of the harvesting machine [18,43,46,51,52]. However, this was also observed in Berendt et al [41], Ghaffariyan et al [53], and Walsh and Strandgard [54]. These studies found that the slope did not significantly impact loaded travel time during extraction activities.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Slope is shown to be a primary factor in productivity because it affects the accessibility of the harvesting machine [18,43,46,51,52]. However, this was also observed in Berendt et al [41], Ghaffariyan et al [53], and Walsh and Strandgard [54]. These studies found that the slope did not significantly impact loaded travel time during extraction activities.…”
Section: Discussionmentioning
confidence: 95%
“…Further, tree volume, instead of DBH, was selected in the regression model because this variable was evaluated as more stable and applicable [17,39,40]. Both the Berendt et al [41] and Han et al [42] studies found that the most commonly used variable is tree volume to estimate the productivity.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanization of timber harvesting commonly involves several challenges: the required equipment is costly [5], and the harvesting activities considerably disturb the forest soil through compaction, rutting and displacement [6]. These activities are even more difficult to conduct on steep terrains due to their inaccessibility to forest vehicles [7].…”
Section: Introductionmentioning
confidence: 99%
“…The study identified a number of factors that negatively affect the implementation of environmental activities, in particular, non-compliance with logging technology and the increase in purchasing prices for raw materials, fuel and lubricants and energy resources [42]. These factors have a significant impact on environmental performance.…”
Section: Accounting Of Environmental Activities In Forestrymentioning
confidence: 99%
“…The improvement and significant growth of economic criteria of efficiency of production and financial activity does not necessarily lead to improvement of environmental performance indicators. A qualitative change in these indicators occurs when the level of utilization of production resources is sufficiently high [42]. It is possible to determine this despite the whole variety of its forms, by using the whole complex of analytical instruments.…”
Section: The Effectiveness Of the Environmental Activitiesmentioning
confidence: 99%